Archaeoastronomy on Inca Sites in the Argentine Northwest. (31st August 2016) - Leibowicz, Ivan; Moyano, Ricardo; Ferrari, Alejandro; Acuto, Félix; Jacob, Cristian
Abstract : In this paper, we present results of astronomical and landscape analysis at four Inca sites located in the Nevados de Cachi area, North Calchaquí Valley, Salta Province, Argentina. Selection criteria took into consideration the existence of certain traits of paramount importance amongst Inca architecture, such as ushnu platforms, gnomons and a particularly interesting petroglyph located in a high-altitude sanctuary. Results show that the location and spatial layout of certain Inca settlements, as well as certain structures within, were designed and located based on astronomical observation patterns centred on solstices, equinoxes and lunar standstills.